Effect of a micro dielectric barrier discharge plasma actuator on quiescent flow. Issue 3 (1st May 2014) - Pescini, Elisa; De Giorgi, Maria Grazia; Francioso, Luca; Sciolti, Aldebara; Ficarella, Antonio
Abstract : A dielectric barrier discharge plasma actuator (PA) was designed and manufactured with microscale dimensions using photolithographic process on fibre glass substrate. AC operation under sinusoidal voltage was investigated experimentally by means of electrical characterisation, smoke flow visualisations and particle image velocimetry. The performances of the micro PA were evaluated and compared with the ones of a macro PA found in this literature. The velocity induced by the micro PA was comparable with the macro PA one, but with lower applied voltage, electrical power dissipation and actuator size. This is particularly interesting for potential applications in turbomachinery.